Antibodies inhibit transmission and aggregation of C9orf72 poly‐GA dipeptide repeat proteins. Issue 5 (28th March 2017) - Zhou, Qihui; Lehmer, Carina; Michaelsen, Meike; Mori, Kohji; Alterauge, Dominik; Baumjohann, Dirk; Schludi, Martin H; Greiling, Johanna; Farny, Daniel; Flatley, Andrew; Feederle, Regina; May, Stephanie; et al.
Abstract: Cell‐to‐cell transmission of protein aggregates is an emerging theme in neurodegenerative disease. Here, we analyze the dipeptide repeat (DPR) proteins that form neuronal inclusions in patients with hexanucleotide repeat expansion C9orf72, the most common known cause of amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). Sense and antisense transcripts of the (G4C2)n repeat are translated by repeat‐associated non‐ATG (RAN) translation in all reading frames into five aggregating DPR proteins. We show that the hydrophobic DPR proteins poly‐GA, poly‐GP, and poly‐PA are transmitted between cells using co‐culture assays and cell extracts. Moreover, uptake or expression of poly‐GA induces nuclear RNA foci in (G4C2)80 ‐expressing cells and patient fibroblasts, suggesting an unexpected positive feedback loop. Exposure to recombinant poly‐GA and cerebellar extracts of C9orf72 patients increases repeat RNA levels and seeds aggregation of all DPR proteins in receiver cells expressing (G4C2)80 . Treatment with anti‐GA antibodies inhibits intracellular poly‐GA aggregation and blocks the seeding activity of C9orf72 brain extracts. Poly‐GA‐directed immunotherapy may thus reduce DPR aggregation and disease progression in C9orf72 ALS/FTD. Synopsis: The pathogenic G4C2 repeat expansion upstream of C9orf72 is bidirectionally transcribed and translated into five aggregating dipeptide repeat proteins (DPRs). Analysis of cell‐to‐cell transmission of DPRs suggests that DPR‐directed antibodies may have therapeutic potential. The hydrophobic DPR species poly‐GA, poly‐GP and poly‐PA are transmitted between cells. Specific antibodies reduce poly‐GA aggregation in cell lines and primary neurons. Poly‐GA antibodies block the seeding activity of C9orf72 brain extracts. Abstract : The pathogenic G4C2 repeat expansion upstream of C9orf72 is bidirectionally transcribed and translated into five aggregating dipeptide repeat proteins (DPRs). Analysis of cell‐to‐cell transmission of DPRs suggests that DPR‐directed antibodies may have therapeutic potential.